Has Housing Filtering Stalled? Heterogeneous Outcomes in the American Housing Survey, 1985-2021 - Spader, Jonathan (Housing policy debate, 2025)
Filtering of housing units-the process through which housing units over time serve occupants with lower or higher incomes-is a primary source of low-cost housing supply in the United States. However, the extent of filtering can vary widely in response to local housing market conditions, and this variation carries implications for the affordable housing strategies used in different areas. This paper uses the American Housing Survey (AHS) panels for 1985-2013 and 2015-2021 to construct repeat income measures of filtering. The analyses then describe the extent of variation in filtering outcomes across time periods, price points, and metropolitan areas. The results show significant variation across all three domains. Temporal analyses document significant changes in the estimated filtering outcomes across multiple time periods. In particular, the estimates for 2015-2021 suggest that downward filtering of housing units stalled or reversed as housing markets tightened in recent years. The direction and extent of filtering is also shown to vary significantly across metropolitan areas with higher and lower home price appreciation. These findings highlight the importance of heterogeneity in filtering outcomes to the conclusions drawn for policy. They also provide insight into the potential limitations of filtering as a source of affordable housing supply.